Learning outcomes and processes in massively multiplayer online games: Exploring the perceptions of players - Voulgari, I.; Komis, V.; Sampson, Demetrios (Springer Boston, 2014)
Over the past decade research has recognised the learning potential of massively multiplayer online games (MMOGs). MMOGs can be used by the technology-enhanced learning research community to study and identify good educational practices that may inspire engaging, creative and motivating approaches for education and learning. To this end, in this research paper, we aim to explore the learning outcomes and processes emerging in the environment of MMOGs by initially studying the relevant perceptions of the players. Based on a theoretical framework referring to the cognitive, the social, and the affective aspects of a technology-supported learning environment, and through a mixed-method research and the analysis of qualitative data from 22 individual and group interviews, and quantitative data from a wider survey (minimum N = 221), we map and examine the cognitive, the skill-based, the social, and the affective potential impact of MMOGs. More specifically this study presents the perceptions of players on the learning impact of MMOGs, the potential transfer of skills to other domains, the learning practices they employ, and elements of the design of the environment that may present positive conditions for learning. We attempt to contribute to the research field and also provide insights for the design of technology-enhanced learning environments, by examining and mapping elements of MMOGs from the perspective of the design of an effective learning environment and based on empirical data. © 2013 Association for Educational Communications and Technology.